Cardiac Cachexia: A Well-Known but Challenging Complication of Heart Failure - Krysztofiak H (Dove Medical Press, 2020)
Helena Krysztofiak,1 Marta Wleklik,2 Jacek Migaj,1,3 Magdalena Dudek,1,3 Izabella Uchmanowicz,2 Magdalena Lisiak,2 Grzegorz Kubielas,2 Ewa Straburzyńska-Migaj,1,3 Maciej Lesiak,1,3 Marta Kałużna-Oleksy1,3 1 1st Department of Cardiology, University of Medical Sciences in Poznan, Poznan, Poland; 2Department of Clinical Nursing, Wroclaw Medical University, Wroclaw, Poland; 3Poznan University of Medical Sciences Hospital of Lord’s Transfiguration, Poznan, PolandCorrespondence:Izabella Uchmanowicz Department of Clinical Nursing, Wroclaw Medical University, Bartla 5, 51-618, Wroclaw, PolandTel +48 71 784 18 05Fax +48 71 345 93 24Email izabella.uchmanowicz@umed.wroc.plAbstract: Heart failure (HF) is a common complication of various cardiac diseases, and its incidence constantly increases. This is caused mainly by aging of populations and improvement in the treatment of coronary artery disease. As HF patients age, they tend to develop comorbidities, creating new problems for health-care professionals. Sarcopenia, defined as the loss of muscle mass and function, and cachexia, defined as weight loss due to an underlying illness, are muscle wasting disorders of particular relevance in the heart failure population, but they go mostly unrecognized. The coexistence of chronic HF and metabolic disorders facilitates the development of cachexia. Cachexia, in turn, significantly worsens a patient’s prognosis and quality of life. The mechanisms underlying cachexia have not been explained yet and require further research. Understanding its background is crucial in the development of treatment strategies to prevent and treat tissue wasting. There are currently no specific European guidelines or recommended therapy for cachexia treatment in HF (“cardiac cachexia”).Keywords: cardiac cachexia, heart failure, nutritional status